Sigfrido : seconda giornata della trilogia: L'anello dei Nibelungi di Riccardo Wagner : sunto della versione ritmica - Zanardini, A.; Wagner, Richard, 1813-1883. (Milano : Stabilimento Musicale Ditta F. Lucca, 1883)
Summary of the Italian libretto by A. Zanardini.
UNC Italian Opera Libretto Collection.
"3-83."
Also available via the World Wide Web.
Mode of access: Internet.
Keywords: Wagner, Richard, -- 1813-1883 -- Stories, plots, etc; Wagner, Richard, -- 1813-1883.; Operas -- Scenarios; Plot summaries